Pintando borboletas : processos educativos dos alunos ciganos - Pinto, Ana Kátia Pereira (2010)
This study aims to evaluate the educational processes of gypsies students. The research was developed from the proposal to understand the culture of this people and to considerate their specific needs. So, the ethnographic study was chosen as the methodological definition. The research, based on observation, was conducted in two Roma/gypsies camps (called “Acampamento Mar” and “Acampamento Terra”) and in two schools (called “CEI Prata” and “Escola Ouro”), both in the city of Fundão, ES. Accordingly, we sought reasons authors in related areas (Sociology and Anthropology) as BOAS, GEERTZ, ELIAS. Field diary and camera were used to record observations. Was supported on theoretical assumptions of CANCLINI, ANDRÉ, MELLO, BORGES to get to know the culture. Was still engaged in dialogue with the authors that base their studies on educational practices as BRANDÃO, MANTOAN, MARTINS. In this movement also seeks justification in Portuguese authors such as COAST, CARDOSO, and FERNANDEZ PEREIRA that subsidize the reflections arising over the course of the study on the educational Gypsies processes, as the Brazilian literature has been scarce in studies on this topic. Seeking to build more opportunities for discussion was also the writings of the gypsy authors BATULI and RUDANA. The study is organized into six chapters which present: a theoretical study on the topic and proposed methodology, the culture of Roma/gypsies, the development of research, observation at “Acampamento Mar”, “Acampamento Terra”, “CEI Prata” and “Escola Ouro”, discussions on the processes observed and the final considerations. As a result, it was concluded that the culture of the Gypsies is not considered in their educational processes in school. It was interpreted that this reflects some factors like lack of teachers on Roma/gypsy, educational practices formatted, crystallized, guided in the way of life for most non- Roma/gypsy. It also showed changes in the culture of Roma/gypsies capixabas and their implications in the education of the same.